Poradnictwo genetyczne i farmakogenetyczne w psychiatrii - Pawlak, Joanna; Twarowska-Hauser, Joanna (Pharmacotherapy in Psychiatry and Neurology/Farmakoterapia w Psychiatrii i Neurologii, 2020)
Genetic research in psychiatry has been developing intensively for over 30 years. The social knowledge on the role of genes in the predisposition to diseases and their importance for treatment effects increases. Psychiatric genetic counselling is a service provided under healthcare around the world. The aim of this pa per is to present psychiatric genetic counselling, its role for patients and its application in the clinical practice at the current state of knowledge. We discuss these aspects of genetic consultation which relate to mental health. Psychiatric genetic counselling is rarely available in the Polish psychiatric care system and access to specialist training is limited. We indicate that the patient’s adap tation to the genetic burden can bring potential bene fits, e.g. better compliance with doctor’s prescriptions. Based on current expert recommendations, we discuss pharmacogenetic tests which are useful in clinical practice. In particular, we analyse the polymorphisms of CYP2D6, CYP2C19 and histocompatibility complex genes HLA.